Prevalence of Eating Disorders in Iran From Preschool to Old Age: A Systematic Review and Meta-analysis - Seyede Hakime Hashemi; Seyed Hamzeh Hosseini; Mahmood Moosazadeh; Marjan Shamspour; Reihaneh Hajizadeh-Zaker; Seyed Bagher Hashemi (Mazandaran University of Medical Sciences, 2022)
Background: Eating disorders are among the deadliest psychiatric diseases that have become increasingly prevalent in different societies in recent years. Various biological, social, and psychological factors are involved in the emergence of different types of eating disorders. Several studies have been conducted by medical and non-medical researchers in Iran to estimate the prevalence of this disorder and its subcategories, which have been associated with different epidemiological methodologies and instruments and inconsistent results.  Objectives: This study aims to statistically analyze all available findings to determine the total estimate of the prevalence of eating disorders in the general population of Iran and to investigate the reasons for the heterogenous results in previous studies. Methods: The articles were collected by searching the following databases: SID, Magiran, Irandoc, Iran Medex, PubMed, and Google Scholar. All studies evaluating the prevalence of eating disorders in any region of Iran from 1990 to the end of 2021 were included in the study. Meanwhile, articles that were irrelevant in terms of subject or methodology were excluded. Three researchers independently extracted the data from the articles based on a pre-prepared list that included the author's name, study title, year of publication, journal name, city and study population, sample size, study instruments, and eating disorder prevalence. Results: The estimated point prevalence of any eating disorder in Iran was 22% (95% CI, 7%-38%). The estimated lifetime prevalence of eating disorder, anorexia nervosa, and bulimia nervosa was 1% (95% CI, 1%-2%), 1% (95% CI, 0%-1%), and 1% (95% CI, 0%-1%), respectively. Conclusions: The prevalence of eating disorders and its subcategories is much lower in Iran compared to high-income and developed countries. The available data are insufficient to determine the exact prevalence of this disorder in the general population, especially among Iranian men.